Transient GUS Expression in Decapitated Lentil Embryos - Hassan, Fathi; Hoque, M Imdadul; Kiesecker, Heiko; Jacobsen, Hans-Jorg (Plant Tissue Culture and Biotechnology, 2008)
Lentil (Lens culinaris Medik.) is an important protein- and carbohydrate-rich food for many developing countries and is also popular in developed countries where they are perceived as a healthy component of the diet. Lentil seeds contain about 24.2% high quality protein, 60% carbohydrates and 2.4 - 4.2% mineral matter (Hulse 1994). Although lentil is one of the oldest cultivated crop plants, its agronomic performance is not better than a semi-domesticated species. The main constraints for lentil breeding and production are poor yield stability and high susceptibility to fungal diseases. Due to the rather narrow genetic base and lack of resistance genes against major fungal diseases in lentil conventional breeding methods cannot be applied for addressing these objectives. In this context the genetic transformation could be used to develop disease resistant plants. Key words: Transient, GUS expression, Lentil embryos DOI = 10.3329/ptcb.v17i1.1126 Plant Tissue Cult. & Biotech. 17(1): 97-102, 2007 (June)